Relationship between fluid leakage and faulting along the western and northern margin of the Hammerfest Basin - Arvo, Jessica (UiT Norges arktiske universitet, 2014)
Abstract This thesis focuses on establishing a causal relationship between potential fluid sources, fluid migration pathways, shallow gas accumulations and potential gas hydrates in the western part of the Hammerfest Basin, SW Barents Sea. Two 3D seismic surveys (LN0901 and ST8320R00) were used to map fluid flow, stratigraphy, structure, fluid flow and other fluid-related features along the western and northern border of the Hammerfest Basin. Furthermore well log data was used to supplement the seismic data and to provide stratigraphic framework of 3D seismic datasets. Widespread fluid flow features, shallow gas accumulation and has hydrates commonly occur in Tertiary succession on the Barents Sea Shelf. These features (especially gas hydrates) have had a growing interest during the last decade as a potential energy resource and as an agent in climate change. Shallow gas accumulations can cause, and have caused, major drilling and engineering hazards around the world. Both hydrates and shallow gas accumulations represent significant geohazards and is therefore important to better understand their occurrence formation mechanism and potential impact on exploration in the SW Barents Sea, a major Norwegian petroleum province. In general three main types of faults are identified between the Hekkingen Formation and the Torsk Formation; these are 1) Large deep-seated faults, 2) Polygonal faults and 3) Smaller shallow faults. The large deep-seated faults are interpreted to be a result of early initiation and later reactivation in two main rift phases. During Late Jurassic- Early Cretaceous period (from c. 160 Ma) a first rift phase probably occurs. Continental rifting continues through the Cretaceous and into Cenozoic. In Plaeocene-Early Eocene another rift-phase occurs. Polygonal faults are interpreted to be a result of dewatering of Late Cretaceous deposits and penetrat into lower Paleocene strata. The smaller, shallow faults could be the result of later smaller tectonic activity and/or from unloading and isostatic ...